Medicinal properties of Morus alba for the control of type 2 diabetes mellitus: a systematic review [version 1; peer review: 2 approved] - Jorge Guillermo Morales Ramos (F1000 Research Ltd, 2021)
Background: The objective of this review was to evaluate the medicinal potential of Morus alba leaves on the control of type 2 diabetes mellitus (DM2). The research question was: what is the therapeutic potential of Morus alba leaves for the control of DM2? Methods: This systematic review was based on the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. The included studies were extracted from Scopus, Pubmed, ScienceDirect, Scielo, and Google Scholar; January 2015 to July 2021. Key search terms were MeSH and DeCS: Morus alba, mulberry, hypoglycemic agent. The inclusion criteria were: studies in rats administered Morus alba leaf extracts; studies that included the dimensions of lipidemia and glycemia; studies that included indicators such as fasting glucose, postprandial glucose, glycosylated hemoglobin, triglycerides, low-density lipoproteins, total cholesterol, and insulin resistance. Exclusion criteria: studies in which Morus alba leaves were administered with other plants; studies with other parts of the Morus alba plant; proteomic studies, cancer, duplicate studies, in vitro studies, and evaluation of included studies. All included investigations were evaluated for biases. Results: Of 253 studies found, 29 were included. The extracts of Morus alba leaves at the phytochemical level improve glucose uptake. Chlorogenic acid, isoquercitrin, and quercitrin, present in the leaves of Morus alba, have hypoglycemic properties and an ameliorating effect on diabetic nephropathy. This leaf has pharmacological effects such as glucose absorption, insulin secretion production, antioxidant and anti-inflammatory agent, antihyperglycemic and antihyperlipidemic activities, and obesity management. Conclusions: Morus alba leaves have pharmacological effects on DM2 that include glucose absorption, production of insulin secretion, antioxidant agent, antihyperglycemic and antihyperlipidemic activities, and obesity control. Beyond these results, there is a lack of studies on the potential and synergistic effects of Morus alba leaves' components, limiting the possibility of a more effective therapy using the plant's leaves.